Identifying the Use Mother Tongue in EFL Classroom: An Observational Study - Noor Wahdi Tamami (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
This study investigates how instructors use their mother tongue in an EFL classroom, which identifies how the instructor uses the mother tongue in the EFL class, regarding its frequency and function. Observational study methods are used in this study. In this study, the researcher observed an instructor in a foreign language class at a junior high school in Yogyakarta. Furthermore, an observation form framework is used to stay focused and the information captured is specific. This study uses an observational framework developed by Paker & Karaağaç (2015). Based on research findings that the use of mother tongue in foreign language classes uses 6 language functions. Of the 6 language functions, the use of the mother tongue is very often used with different purposes but still the mother tongue has a role as a liaison for the target language in order to achieve learning objectives in the classroom.